TOPONIMIA DEPRESIUNILOR SIBIULUI ŞI FĂGĂRAŞULUI, REFLECTARE FIDELĂ A CONDIŢIILOR GEOGRAFICE ŞI ISTORICE (PANGEEA, 2025)
This sequel to my article on Oikonyms in the Sibiu and Făgăraş Depressions – an accurate reflection of geographical and historical conditions, published in "Geo-Carpathica", X, 10, 2010, enlarges the sphere of a total of 400 place-names, with 158 landforms, 123 water courses, 8 forests and 4 old roads. As the region has friendly geographical conditions it has been inhabited since ancient times. The 293 toponyms analysed in this paper are a faithful reflection of past geographical historical and social events in the region. Thus, 96 names designate landforms and running waters, 58 stand for vegetation, 18 for the fauna, 28 for land-use practices and 10 for people's occupations; 14 recall historical and social-life events and 4 old roads. Most of them (257) are of Romanian origin, having been given by the native population of the region, who has been living here from oldest times. A few toponyms originate from Old Slav (14), Hungarian (11), German (10) and Thraco-Getae-Dacian (1). But for some exceptions, dating to the remote past when the Hungarian administration had replaced Romanian and German toponyms by Magyar ones, or to the near past when Romanian names were substitued for some German ones, the basic name-stock in the Sibiu and Făgăraş Depressions has not been substantially changed. In a view of the above, it is our duty to undertake a careful study and offer the most reliable geographical historical and linguistic explanation of the reality on the ground.